Pengaruh Potongan Harga, Kualitas Pelayanan dan Penanganan Komplain terhadap Kepuasan Pelanggan Pengguna Gojek - Sindi Emya Br Ginting; Harris P Nasution; Erwinsyah Simanungkalit; Indra Siregar; Enda Surbakti (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2024)
Customer satisfaction is the hope of a customer who believes or predicts what the customer will receive, whether expressed verbally or non-verbally. Customers who obtain satisfaction are determined from repurchasing products or services. Customer satisfaction can be met by price discounts, service quality and complaint handling. The aim of this research is to determine and analyze the influence of price discounts, service quality and complaint handling on customer satisfaction of Gojek users. The population used in this research were students majoring in Business Administration, Medan State Polytechnic. The number of respondents consisted of 96 people, with the determination of sample size using the Lemeshow formula. The results of the t test (partial test) for the price discount variable on customer satisfaction (Y) obtained a calculated of 2,843 > 1,986 with a significance level of 0,006 < 0,05 and a positive regression coefficient of 0,350. This means that the price discount has a positive and significant effect on customer satisfaction (Y). The results of the t test (partial test) for the service quality variable on customer satisfaction (Y) obtained a calculated of 2,955 > 1,986 with a significance level of 0.004 < 0.05 and a positive regression coefficient of 0.208. This means that service quality has a positive and significant effect on customer satisfaction (Y). The results of the t test (partial test) for the complaint handling variable on customer satisfaction (Y) obtained a calculated of 4,116 > 1,986 with a significance level of 0.000 < 0.05 and a positive regression coefficient of 0,332. This means that complaint handling has a positive and significant effect on customer satisfaction (Y). The results of the F test (simultaneous test) are a calculated of 61,481 > 2,70 with a significance level of 0.000 < 0.05, which indicates that the F value obtained is significant. This means that there is a variable influence of price discounts, service quality and complaint handling on customer satisfaction.